Theory and methods for supporting high level military decisionmaking - Davis, Paul K., 1943-; Kahan, James P.; Rand eBooks (Santa Monica, CA : RAND, 2007)
This report describes an approach to high-level decision support for a Joint Forces Air Component Commander in combat operations or a Chief of Staff in defense planning. Its central theme is the fundamental importance of dealing effectively with uncertainty, whether in effects-based operations, building the Air Force's Commander's Predictive Environment, or planning future forces with the methods of capabilities-based planning. Because many features of the future cannot be predicted with reasonable confidence, it is better to proceed with the expectation of surprise developments and to have skill in recognizing adaptations and making them than it is to treat uncertainty merely as an annoyance. This report sketches the framework of a high-level decision-support environment that is top-down, expresses concepts in simple and intuitive language, deals explicitly with risk and uncertainty, and provides the capability for decisionmakers to readily discover and question the bases for key assumptions and assessments. It can accommodate both "rational-analytic" and "naturalistic" decisionmakers, allowing them to produce strategies that are flexible, adaptive, and robust (FAR). Two explicit methods and their related tools are described. The first involves portfolio-style thinking and analysis, a good mechanism for balancing risks and other considerations in choosing a course of action. The second is a novel modification of foresight exercises that addresses the need to include humans effectively in dealing with uncertainty. A more extensive discussion of available methods and enabling technologies is also presented, along with some recommendations about investment priorities.
Introduction -- Uncertainty, Risk, and Choice -- Reconciling Different Approaches to Decisionmaking -- A Framework for High-Level Decision Support -- Examples of New Tools -- Priorities for Investment in Families of Models, Games, and Other Tools -- Conclusions -- Appendix: Issues and Controversies Regarding Effects-Based Operations and the Commanderb2(Bs Predictive Environment.s
Includes bibliographical references (p. 71-77).
Also available on the internet via WWW in PDF format.
Keywords: Command of troops; Decision making -- Methodology; Military planning -- Decision making; Electronic books